THE PROBLEMS OF QUALITY EMPIRICAL RESEARCH - M. Yurasova (Вестник университета)
The subject of this article is to provide the quality of empirical research. The purpose of the article is to review the methods and quality control techniques of empirical research. The article deals with the quality of applied sociological and marketing research, reviewed the provisions of international standards related to market research, public opinion and social problems; shows the basic requirements for the quality performance of research; considered examples of the quality of analysis and rating of research companies. The paper provides recommendations on the use of various technologies in the practice of empirical research. Key findings and recommendations formulated as the need to build the research process, including the control of performers with regard to minimize the errors committed by executors.